Management of Banana Xanthomonas Wilt: Evidence from impact of adoption of cultural control practices in Uganda - Kikulwe, Enoch M.; Kyanjo, Joseph Lule; Kato, Edward; Ssali, Reuben T.; Erima, Rockefeller (MDPI, 2019)
Banana Xanthomonas Wilt (BXW) is an important emerging and non-curable infectious plant pathogen in sub-Saharan Africa that can cause up to 100% yield loss, negatively impacting sustainable access to food and income to more than 100 million banana farmers. This study disentangles adopters into partial and full adopters to investigate the factors that are relevant to sustain the adoption process of BXW control practices and quantifies the impact of adopting the practices. Data from a randomly selected sample of 1200 banana farmers in Uganda where the disease is endemic was used. A multinomial logit model was used to determine the factors affecting adoption of control practices and augmented inverse probability weighting was employed to estimate the impacts of adoption on banana productivity and sales. Results show that training a woman farmer and having diverse sources of information about BXW control practices increased adoption of the control practices and reduced the disease incidences. Farmers who adopted all the recommended control practices achieved significantly the highest values of banana production and sales. We conclude that improving information access through farmers’ preferred communication channels, having women-inclusive trainings, and a combination of cultural practices are effective ways for sustaining adoption of the control practices.